2021
DOI: 10.3389/fimmu.2021.769685
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Subtypes and a Prognostic Signature Based on Inflammation-Related Genes in Colon Adenocarcinoma

Abstract: Both tumour-infiltrating immune cells and inflammation-related genes that can mediate immune infiltration contribute to the initiation and prognosis of patients with colon cancer. In this study, we developed a method to predict the survival outcomes among colon cancer patients and direct immunotherapy and chemotherapy. We obtained patient data from The Cancer Genome Atlas (TCGA) and captured inflammation-related genes from the GeneCards database. The package “ConsensusClusterPlus” was used to generate molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Using R software package ConsensusClusterPlus (v1.54.0) ( Qiu et al, 2021 ) for consistency analysis, the maximum number of clusters was 6, 100 times repeated, 80% of the total sample. The clustering map was analyzed by R software package pheatmap (v1.0.12), and the genes with variance above 0.1 were retained in the gene expression maps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using R software package ConsensusClusterPlus (v1.54.0) ( Qiu et al, 2021 ) for consistency analysis, the maximum number of clusters was 6, 100 times repeated, 80% of the total sample. The clustering map was analyzed by R software package pheatmap (v1.0.12), and the genes with variance above 0.1 were retained in the gene expression maps.…”
Section: Methodsmentioning
confidence: 99%
“…Least absolute shrinkage and selection operator (LASSO) regression algorithm ( Yi et al, 2020 ) was used for feature selection, and 10 times cross validation was used. R software package glmnet ( Qiu et al, 2021 ) was used for the above analysis. Log-rank was used to test KM survival analysis to compare survival differences between the above two groups or groups.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the patients in the low-risk group had better OS than those in the highrisk group in the training cohort, validation cohort, and entire cohort. The AUC values for 3-year survival in the training cohort and validation cohort were 0.74 and 0.67, respectively, indicating that the model has better predictive ability than similar prognostic models in other studies (AUC = 0.63, AUC = 0.585) (36,37). Then, we identified the risk score as an independent prognostic factor by univariate and multivariate Cox regression analyses.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, univariate and multivariate Cox regression analyses and ROC curves confirmed that the risk score based on the expression of 13 IFN-γ-related lncRNAs could predict patient prognosis independently of traditional clinical characteristics, which demonstrated the universal applicability of the risk score. The AUC values for 3-year OS in the training cohort and validation cohort were 0.792 and 0.698, respectively, indicating better predictive power compared with other similar prognostic signatures (AUC=0.585, AUC=0.63) ( 25 , 26 ). In addition, the calibration curve showed that the actual observation vs. prediction rates of 1-, 3- and 5-year OS demonstrated a good consensus.…”
Section: Discussionmentioning
confidence: 87%